Blended Learning and digital education of university teaching staff - Balladares Burgos, Jorge (2020)
Blended learning is an integrating education program that combines computer-based activities with regular classes. It contributes to the quality of higher education through the improvement of ICT training programs and the development of e-competences in higher education. There has been a literature review of different bibliographic sources related to b-learning and Teaching Professional Development.   As a result of this review, it is perceived that e-learning training programs are not efficient enough to face the challenges of blended education, and Blended Learning could be an alternative for teacher online professional development. Then, research results of the incidence of an ICT training course for higher education professors are shown. It is concluded that blended learning is an effective modality for teachers' digital education courses because the face-to-face component complements virtual learning.  In addition, due to problems of connectivity and access to internet, b-learning modality is an alternative for the continuing education of higher education professors.